Risk Factors, Management, and Outcomes of Bile Duct Injury Following Cholecystectomy in a Tertiary Centre: A 9-Year Retrospective Analysis in Sulaimani City, Iraq - Mohammed, Dara Ahmed (Journal of Sulaimani Medical College, 2025)
Background: The bile duct injury is a common complication of cholecystectomy especially for laparoscopic cholecytectomy. National literatures evaluating features, management and outcomes are scarce. Objective: To identify risk factors, types, method of management and outcome of bile duct injury after cholecystectomy. Methodology: Present study was a retrospective cross sectional study implemented in the Kurdistan centre of Gastroenterology and Hepatology (KCGH) in Sulaimani city, Kurdistan region-Iraq through the period of 9 years from 1st of January 2015, to 31st of December, 2023 on sample of 75 patients with bile duct injury. The patients characteristics, surgical operation features and outcomes were assessed directly by the researcher. The patients were followed up for at least twelve months postoperatively. The researchers reviewed the data at entry until discharge from KCGH and follow up of data for at least one year postoperatively. The diagnosis was done according to clinical and radiological investigation. Results: Bile duct injury types according to Strasberg classifications were type A (20%), type C (4%), type D (9.3%), type E1 (21.3%), type E2 (20%), type E3 (18.7%) and type E4 (6.7%). The common cause of injury was beginner surgeon (50.7%). The main management methods implemented for bile duct injury repair were Roux-en-y-hepatico-jejnjunostomy (68.1%) and ERCP with stent (17.3%). The rural places, beginner surgeons, late diagnosis, bile peritonitis presentation, advanced Strasberg classification and Roux-en-y-hepatico-jejnjunostomy management method were significantly related to poor outcomes of bile duct injury repair. Conclusions: The bile duct injury risk factors, types, method of management and outcome of bile duct injury after cholecystectomy are comparable to high resources countries.
Keywords: Laparoscopic cholecystectomy; Bile duct injury; Outcome